2021
DOI: 10.1097/nmd.0000000000001308
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in the Time of Corona

Abstract: The recent COVID-19 pandemic is having profound impacts on every sector of society, and New York City (NYC) emerged as an early epicenter of the disease. Given the novelty and scale of the disease, information surrounding COVID-19 has been marked by considerable uncertainty and confusion. Although various factors have been associated with COVID-19 distress, little is known about the relations between levels of intolerance of uncertainty (IU) and anxiety symptoms and behaviors. This cross-sectional study sought… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…In line with previous findings, we found that the specific fear of COVID-19 is strongly associated with high acceptance and adherence to the preventive measures (e.g., Carlucci et al, 2020;Jiwani et al, 2021;Kachanoff et al, 2021;Plohl & Musil, 2021;Reinders Folmer et al, 2020;Rothgerber et al, 2020;Vally, 2020). Fear of COVID-19 was also intercorrelated with fear of death and trait anxiety, and the latter tended to be positively associated with acceptance of the preventive measures.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with previous findings, we found that the specific fear of COVID-19 is strongly associated with high acceptance and adherence to the preventive measures (e.g., Carlucci et al, 2020;Jiwani et al, 2021;Kachanoff et al, 2021;Plohl & Musil, 2021;Reinders Folmer et al, 2020;Rothgerber et al, 2020;Vally, 2020). Fear of COVID-19 was also intercorrelated with fear of death and trait anxiety, and the latter tended to be positively associated with acceptance of the preventive measures.…”
Section: Discussionsupporting
confidence: 91%
“…However, fear of COVID-19 was the only fear-related variable that was associated with adherence to the preventive measures. The separate assessment of acceptance and adherence might help to explain previous mixed results regarding the role of trait anxiety (e.g., Ebrahimi et al, 2020;Jiwani et al, 2021;Siebenhaar et al, 2020). Specifically, our results indicate that trait anxiety influences how the pandemic situation is perceived and consequently shapes the attitude towards the preventive measures (Erceg et al, 2020;Sweeny & Dooley, 2017), but only the specific fear of COVID-19 is a reliable determinant of the actual preventive behaviour.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations